PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM INDUSTRI PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN TERHADAP BEI PERIODE 2018-2021 - Rumapea, Hizkia; Kaban, Marsena; Br Sinaga, Jholant Bringg Luck Amelia; br Ginting, Bena (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The purpose of this study was to see Pengaruh Return on Asset (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), dan Net Profit Margin (NPM) Against the industrial share price of food and beverage subsector manufacturing companies on the IDX for the 2018-2021 period. The type of research used for this study is quantitative research, the source of data in this study is secondary research. The population of this study obtained 26 companies that were included in the listed criteria and 2 that did not include the criteria and listed companies were reduced by those that were not listed, the result was 24 and multiplied by 4 years to 96. The data collection technique used in this study was to use F test data and t test at a significant level of 5% and coefficient of determination. Based on the results of this study partially and simultaneously that variable X (Return on asset (ROA), Return on Equity (ROE), Debt to Equity ratio (DER), dan Net Profit Margin (NPM)) significant influence on variable Y (stock price).